2009
DOI: 10.1111/j.1551-2916.2009.03022.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Seed Layer Characteristics on the Synthesis of ZnO Nanowires

Abstract: Single crystalline zinc oxide (ZnO) nanowires were synthesized on sputter‐deposited ZnO seed layers via hydrothermal reactions in an equimolar (20 mM) aqueous solutions of Zn(NO3)2·6H2O and C6H12N4 at 90°C. The sputter‐deposited ZnO seed layers were prepared to exhibit different crystalline structures in order to examine their effects on the growth of ZnO nanowires. It was found that the nanowire diameter depends on the size of the (002) grains of the seed layer. This is attributed to the epitaxially growth of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
45
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 28 publications
5
45
0
Order By: Relevance
“…ZnO nanostructures have attracted more attentions for their applications in various nanodevices including nanogenerators, light-emitting diodes, polarization sensitive photodetectors, nanolasers, chemical sensors and solar cells [8][9][10][11][12][13][14][15][16][17][18]. Various synthesis methods such as thermal evaporation, chemical vapor deposition, metal-organic chemical vapor deposition, molecular beam epitaxy, template-assisted methods, electrochemical deposition and hydrothermal/solvothermal methods have been successfully applied in syntheses of ZnO nanostructures [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Among these synthesis routes, hydrothermal/solvothermal syntheses are the most low-cost, simple, large-scale, and practical methods.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO nanostructures have attracted more attentions for their applications in various nanodevices including nanogenerators, light-emitting diodes, polarization sensitive photodetectors, nanolasers, chemical sensors and solar cells [8][9][10][11][12][13][14][15][16][17][18]. Various synthesis methods such as thermal evaporation, chemical vapor deposition, metal-organic chemical vapor deposition, molecular beam epitaxy, template-assisted methods, electrochemical deposition and hydrothermal/solvothermal methods have been successfully applied in syntheses of ZnO nanostructures [19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Among these synthesis routes, hydrothermal/solvothermal syntheses are the most low-cost, simple, large-scale, and practical methods.…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that ZnO NRs epitaxially grow on the polycrystalline ZnO seeds. [22][23][24][25] In contrast, the present work demonstrates that the crystallite orientation can be readily tuned by altering the solvent composition. Note also that no PO is developed in the ZnO seed layer.…”
Section: Discussionmentioning
confidence: 70%
“…However, the nucleation mechanism of ZnO NRs on the seed layer has not yet been clearly understood. It has been proposed that ZnO NRs epitaxially grow on the polycrystalline ZnO seeds …”
Section: Discussionmentioning
confidence: 99%
“…In this process, equimolar solutions of zinc nitrate hexahydrate ˚C for 3h which was 12 degrees less than what was reported in the literature [19]. The substrates were then removed and washed with deionized water to eliminate any residual salt and later dried in air at room temperature.…”
Section: Growth Of Zno Nanorodsmentioning
confidence: 98%
“…Whereas other techniques usually require high temperature, catalysts, high experimental costs and complicated equipment [11] .In order to achieve well-aligned ZnO nanorods, it is important to apply the deposition on an appropriate seed layer since researches have reported that ZnO nanorods grow epitaxially from the columnar grains of a seed layer [17][18][19]. There are two most commonly routes used to obtain a ZnO seed layer; sol-gel method and radio frequency (RF) sputtering process [21].…”
Section: Introductionmentioning
confidence: 99%